Seni Tari Kontemporer Sebagai Art Therapy dalam Mendukung Perkembangan Psikomotor dan Emosional Siswa Tunagrahita Ringan - Rizky Nurul Khotimah; Jaeni Jaeni; Yahfenel Evi Fussalam (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Inclusive education requires learning approaches that are not solely oriented toward academic achievement but are also capable of supporting the psychomotor and emotional development of students with special needs, including those with mild intellectual disabilities. Students with mild intellectual disabilities commonly experience limitations in motor coordination, emotional regulation, and attention focus, which necessitate adaptive, holistic, and experiential learning strategies. This study aims to describe the implementation of contemporary dance as an art therapy approach in supporting the psychomotor and emotional development of students with mild intellectual disabilities in an inclusive school setting. The study employed a quantitative approach using a Single Subject Research (SSR) method with an A–B–A design. The research subject was one ninth-grade student with mild intellectual disability at SMPN 1 Karangtengah. Data were collected through systematic observation during the baseline-1 (A-1), intervention (B), and baseline-2 (A-2) phases, using indicators of psychomotor and emotional development. The results showed improvements in motor coordination, movement fluency and balance, imitation ability, attention focus, and emotional expression during the intervention phase. In the baseline-2 phase, most of the acquired abilities were maintained despite the termination of the intervention, indicating stability in behavioral changes. These findings suggest that contemporary dance as an art therapy approach has the potential to serve as a relevant and effective pedagogical-therapeutic strategy in supporting the psychomotor and emotional development of students with mild intellectual disabilities. The implications of this study indicate that contemporary dance can be integrated into arts learning or Individualized Education Programs as a humanistic learning alternative oriented toward students’ developmental needs within inclusive education contexts.